The protein transition: what determines the animal-to-plant (A:P) protein ratios in global diets - Drewnowski, Adam; Hooker, Kayla (Frontiers in Nutrition, 2025)
BackgroundSeveral high-income countries have announced plans to reduce the animal-to-plant (A:P) protein ratios in their population diets. Their current A:P ratio is around 65:35, with two thirds of the protein coming from animal sources, meat, eggs, and dairy. Efforts to reduce the dietary A:P protein ratio to 50:50, 40:60, or below are sometimes referred to as a “healthy protein transition.”MethodsAnalyses of Food and Agriculture Organization (FAO) and World Bank data were used to show that an opposing and far more important protein transition is taking place globally.ResultsIn most low- and middle-income countries (LMIC), the dietary A:P protein ratio was closely associated with, if not determined, by gross national incomes (GNI). As incomes rise, LMIC populations adopt more varied and more nutrient-rich diets with more animal proteins and especially meat. This protein transition, manifested by a strong observed relation between rising incomes and higher A:P protein ratios, follows a well-known principle of economics known as Bennett’s Law.ConclusionConsumer education and regulatory and policy measures aimed at reducing dietary A:P protein ratios worldwide may not uncouple the fundamental relation between powerful economic forces and global diet structures.